EFFECTS OF SCIENTIFIC INQUIRY LEARNING MODEL AND LOGICAL THINKING ABILITY OF HIGH SCHOOL STUDENTS SCIENCE PROCESS SKILLS - M. Akhyar Lubis; Mara Bangun Harahap; Sondang R. Manurung (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This study aimed to analyze whether the results of science process skills of students. Who are taught by the teaching model scientific inquiry better than conventional learning, to analyze whether the results of science process skills of students? Who can think logically high is better than the students who have the potential to think logically low, analyze whether there is an interaction between scientific inquiry learning model with logical thinking skills to students' science process skills. This research is a quasi-experimental design with the two-group pretest-posttest design. The study population is all students of class X SMA Negeri 4 Padangsidimpuan semester II academic year 2016/2017. The The research instrument consists of two types: science process skills instrument consists of 10 questions in essay form which has been declared valid and reliable, and the instrument ability to think logically in the form of multiple choice is entirely groundless and complements (combination). The resulting data, analyzed by using two path Anava. The results showed that science process skills of students who are taught by the teaching model scientific inquiry better than conventional learning. Science process skills of students who can think logically high are better than the students who can think logically low, and there is an interaction between learning model scientific inquiry and conventional learning with the ability to think logically to improve students' science process skills.